Letter : Certificate of insurance
030-0023-001 TELEGRAPHIC ADDRESS "SOCIETY, GLASGOW" TELEPHONE NO. 2100 SOUTH SCOTTISH CO-OPERATIVE WHOLESALE SOCIETY LTD. CENTRAL OFFICES 95 MORRISON ST. GLASGOW. C.5 IN YOUR REPLY REFER TO A/TCD/IEF. All letters to be addressed to the Society, and not to Individuals 17th October, 1938 The National Council of Labour c/o Trades Union Congress, 33 Elmbank Street, GLASGOW, C.2. 18 OCT 1938 Certificate of Insurance. We hereby certify that we have insured for your account, under Marine Insurance (F.P.A.) and War Risk covers, at Lloyds, a consignment of foodstuffs, shipped from Glasgow to Valencia, Spain, per S.S. "Stangate " to the value of £1,500. Original policies are in our possession, and any claim for damage arising therefrom should be notified to us at the earliest possible date. Per SCOTTISH CO-OPERATIVE WHOLESALE LIMITED [signed] Accountant 292/946/30/23